Evolution of Inflammatory Bowel Disease Research From a Bird's-Eye Perspective: A Text-Mining Analysis of Publication Trends and Topics. Issue 3 (22nd May 2020) - Barash, Yiftach; Klang, Eyal; Tau, Noam; Ben-Horin, Shomron; Mahajna, Hussein; Levartovsky, Asaf; Arebi, Naila; Soffer, Shelly; Kopylov, Uri
Abstract : This work presents a bird's-eye perspective on 25 years of research in the field of inflammatory bowel disease. It analyzes trends in the number of publications, main topic, manuscript country of origin, and main therapeutic agents in research. Abstract: Background and aim: Inflammatory bowel disease (IBD) research is extensive and increasing, with topics varying and shifting foci over time. A comprehensive analysis of the trends in IBD publications may help us grasp knowledge gaps and map future areas of interest. The aim of our study was to create a map of IBD research for the last 25 years using computational text-mining techniques. Methods: We retrieved all available MEDLINE/PubMed annual datasets between 1992 and 2016. We categorized article characteristics by using word combination and title match techniques. We also assigned country of origin for each article from the first author's affiliation. Results: During the study period, 18, 653 publications that appeared on PubMed were classified as IBD-related. The annual number of publications increased almost 4-fold (354 to 1361) during the study period. The United States had the highest total number of publications (n = 3179/16, 358, 19.4%) and Denmark, Sweden, and Israel had the highest rate of publications per capita. There were 7986 articles successfully assigned with a main subject. Therapeutics, surgical treatment, and endoscopy were the 3 leading topics, with n = 2432/7986 (30%), 1707/7986 (21%), and 981/7986 (12%), respectively. When analyzing trends in topics over time, we found an increase in the proportion of articles on imaging (2.2% in 1992-1996 to 8% in 2012-2016) and a decrease in the proportion of articles on surgical treatment (30% in 1992-1996 to 19% in 2012-2016). Conclusions: There is steady increase in the number of IBD-related publications. Although the United States is a world leader in the number of IBD publications, Denmark, Sweden, and Israel publish the most per population size. Medical therapeutics is the most popular topic, yet there is a steady increase in publications devoted to imaging and monitoring.